Pelatihan Manajemen Zakat untuk Pengurus Masjid pada PCM Slipi, Jakarta Barat - Rito, Rito; Nuryadin, Deni (Faculty of Economics and Business, University of Muhammadiyah Prof. DR. HAMKA, 2020)
The mosque is a place of worship for Muslims. It is where various community activities take place. The mosque is also a place for managing zakat funds from and for the community. The funds collected can be redistributed to the community in accordance with the 8 asnaf found in the Quran. PCM Pamulang is located in the city of Tangerang. The mosque in PCM Slii, West Jakarta is a significant location for zakat management training. Mosque administrators can be used as resources that can be developed in understanding the management of zakat. In this research, a team that just received NIDN was involved, namely Mr. Rito, SE, Ak, MSi, CA. This is intended to invite new lecturers to be active in the chess darma of higher education.